Synthesis, structure and bioactivity of Ni2+ and Cu2+ acylhydrazone complexes. Issue 7 (14th June 2019) - Xie, Long-Yan; Zhang, Yu; Xu, Hao; Gong, Chang-Da; Du, Xiu-Li; Li, Yang; Wang, Meng; Qin, Jie
Abstract : Mononuclear [Ni( L )2 ] and dinuclear [Cu( L )(μ1, 1 ‐N3 )]2 types of complexes were obtained from N, N ′, O ‐donor acylhydrazone ligand H L . The two complexes show potent urease inhibitory activity and suitable binding affinity to BSA. Abstract : Two acylhydrazone complexes, bis{6‐methyl‐ N ′‐[1‐(pyrazin‐2‐yl‐κ N 1 )ethylidene]nicotinohydrazidato‐κ 2 N ′, O }nickel(II), [Ni(C13 H12 N5 O)2 ], (I), and di‐μ‐azido‐κ 4 N 1 : N 1 ‐bis({6‐methyl‐ N ′‐[1‐(pyrazin‐2‐yl‐κ N 1 )ethylidene]nicotinohydrazidato‐κ 2 N ′, O }nickel(II)), [Cu2 (C13 H12 N5 O)2 (N3 )2 ], (II), derived from 6‐methyl‐ N ′‐[1‐(pyrazin‐2‐yl)ethylidene]nicotinohydrazide (H L ) and azide salts, have been synthesized. H L acts as an N, N ′, O ‐tridentate ligand in both complexes. Complex (I) crystallizes in the orthorhombic space group Pbcn and has a mononuclear structure, the azide co‐ligand is not involved in crystallization and the Ni 2+ centre lies in a distorted N4 O2 octahedral coordination environment. Complex (II) crystallizes in the triclinic space group P and is a centrosymmetric binuclear complex with a crystallographically independent Cu 2+ centre coordinating to three donor atoms from the deprotonated L − ligand and to two N atoms belonging to two bridging azide anions. The two‐ and one‐dimensional supramolecular structures are constructed by hydrogen‐bonding interactions in (I) and (II), respectively. The in vitro urease inhibitory evaluation revealed that complex (II) showed a better inhibitory activity, with the IC50 value being 1.32±0.4 µ M . Both complexes can effectively bind to bovine serum albumin (BSA) by 1:1 binding, which was assessed via tryptophan emission–quenching measurements. The bioactivities of the two complexes towards jack bean urease were also studied by molecular docking. The effects of the metal ions and the coordination environments in the two complexes on in vitro urease inhibitory activity are preliminarily discussed.